Reciprocal Hosts' Responses to Powdery Mildew Isolates Originating from Domesticated Wheats and Their Wild Progenitor - Ben-David, Roi; Dinoor, Amos; Peleg, Zvi; Fahima, Tzion (Frontiers in Plant Science, 2018)
The biotroph wheat powdery mildew, Blumeria graminis (DC.) E.O. Speer, f. sp. tritici Em. Marchal (Bgt), has undergone long and dynamic co-evolution with its host. In the last 10,000 years, processes involved in plant evolution under domestication, altered host-population structure. Recently Both virulence and genomic profiling separated Bgt into two groups based on their origin from domestic host and from wild emmer wheat. While most studies focused on Bgt pathogen, there is significant knowledge gaps in the role of wheat host diversity in this specification. This study aimed to fill this gap by exploring qualitatively and also quantitatively the disease response of diverse host panel to powdery mildew [105 domesticated wheat genotypes (Triticum turgidum ssp. dicoccum, T. turgidum ssp. durum and T. aestivum) and 241 accessions of its direct progenitor, wild emmer wheat (T. turgidum ssp. dicoccoides)]. A set of eight Bgt isolates, originally collected from domesticated and wild wheat was used for screening this wheat collection. The isolates from domesticated wheat elicited susceptible to moderate plant responses on domesticated wheat lines and high resistance on wild genotypes (51.7% of the tested lines were resistant). Isolates from wild emmer elicited reciprocal disease responses: high resistance of domesticated germplasm and high susceptibility of the wild material (their original host). Analysis of variance of the quantitative phenotypic responses showed a significant Isolates × Host species interaction (P(F) <.0001) and further supported these findings. Furthermore, analysis of the range of disease severity values showed that when the group of host genotypes was inoculated with Bgt isolate from the reciprocal host, coefficient of variation was significantly higher than when inoculated with its own isolates. This trend was attributed to the role of major resistance genes in the latter scenario (high proportion of complete resistance). By testing the association between disease severity and geographical distance from the source of inoculum, we have found higher susceptibility in wild emmer close to the source. Both qualitative and quantitative assays showed a reciprocal resistance pattern in the wheat host and are well aligned with the recent findings of significant differentiation into wild-emmer and domesticated-wheat populations in the pathogen.